Healthy lifestyle and genomic ancestry related to good glycemic control in type 1 diabetes patients from Northeastern Brazil: a hierarchical analysis - de Sousa Azulay, Rossana Santiago; Rodrigues, Vandilson; França de Abreu, Joana D’Arc Matos; Pereira de Almeida, Ana Gregória Ferreira; Lago, Débora; Tavares, Maria da Glória; Nascimento, Gilvan; Rocha, Viviane; Magalhães, Marcelo; Facundo, Alexandre; de Oliveira Neto, Clariano Pires; Guimarães Sá, Adriana; et al. (Frontiers in Endocrinology, 2023)
This study aimed to investigate the sociodemographic factors, dietary adherence, regular physical activity, and genomic ancestry percentage associated with good glycemic control in Brazilian patients with type 1 diabetes (T1D) using a hierarchical approach. Methods: A cross-sectional study was conducted in 152 T1D patients. Glycated hemoglobin (HbA1C) levels were measured to evaluate the glycemic control status (good, moderate, or poor). Independent factors included sex, age, selfreported skin color, educational level, family income, dietary patterns, and physical activity. The percentage of genomic ancestry (Native American, European, and African) was influenced by a panel of 46 autosomal insertion/deletion ancestry markers. Statistical analyses included receiver operating characteristic curves, and hierarchical logistic regression analysis. Results: The hierarchical analysis, patients who had high dietary adherence showed a positive association with good glycemic control (adjustedOR = 2.56, 95% CI:1.18-5.59, P = 0.016). Thus, age greater than 40 years was associated with good glycemic control compared to the children and adolescents group (adjustedOR = 4.55, 95% CI:1.14-18.1, P = 0.031). Males were associated with good glycemic control (adjustedOR = 2.00, 95% CI:1.01-4.00, P =0.047). Conclusion: The study findings suggest that consistent adherence to dietary regimens is associated with good glycemic control after adjusting for sociodemographic and genomic ancestry factors in an admixed population of T1D patients from Northeast Brazil.